Tú, Usted and the construction of male heterosexuality in young, working class men in Tolima (2017)
This article examines the relationship between the use of the pronoun tú among working-class men and the perceived homosexuality of its use. In Colombia, the use of tú and ustedamong men is often a carefully considered linguistic choice, one that is tied to sexual identity and gender. While statistical studies have been done looking at this trend, prior research had not examined the reasoning behind this choice. In modern sociolinguistics and sociology, heterosexuality is not seen as a fixed aspect of a person’s being, but as a social identity that is managed through discourse. Embarking from Social Identity Theory, this research used a series of 20 extensive ethnographic interviews in Tolima, Colombia to explore the connection between heterosexuality and pronoun selection. After analysis using grounded theory, the article examines the idea that it is not homosexuality but heterosexuality that is constructed through careful pronoun use and that heterosexuality is actually a delicate construction. In this context, the article concludes that the sociolinguistic function of tú and usted is to serve as contextualization cues for the social distance required for men’s heterosexual social identity.